To solve the equation \( 34 = -(m + 3) \), we can follow these steps:
Step 1: Distribute the Negative Sign
The first step is to rewrite the equation by distributing the negative sign on the right-hand side.
\[ 34 = -1 \cdot (m + 3) \]
This gives us:
\[ 34 = -m - 3 \]
Step 2: Isolate the Variable Term
Next, we want to get all the terms involving \( m \) on one side and the constant terms on the other side. We can do this by adding 3 to both sides of the equation.
\[ 34 + 3 = -m \]
So, we have:
\[ 37 = -m \]
Step 3: Solve for \( m \)
To solve for \( m \), we can multiply both sides of the equation by -1 to isolate \( m \).
\[ m = -37 \]
Step 4: Verify the Solution
Finally, we can check our work by substituting \( m = -37 \) back into the original equation to ensure both sides are equal.
Starting with the original equation:
\[ 34 = -(m + 3) \]
Substituting \( m = -37 \):
\[ 34 = -((-37) + 3) \] \[ 34 = -(-34) \] \[ 34 = 34 \]
Since both sides are equal, the solution is verified.
Summary of Steps
- Distribute the negative sign: \( 34 = -m - 3 \).
- Isolate the variable: \( 37 = -m \).
- Solve for \( m \): \( m = -37 \).
- Verify the solution by substituting \( m \) back into the original equation.
The final solution is:
\[ \boxed{-37} \]